2017
DOI: 10.22605/rrh4044
|View full text |Cite
|
Sign up to set email alerts
|

The Pituri Learning Circle: central Australian Aboriginal women’s knowledge and practices around the use of Nicotiana spp. as a chewing tobacco

Abstract: Introduction: Tobacco smoking has a range of known and predictable adverse outcomes, and across the world sustained smoking reduction campaigns are targeted towards reducing individual and public risk and harm. Conversely, more than 87 million women, mostly in low-and middle-income countries, use smokeless tobacco, yet the research examining the effect of this form of tobacco exposure on women is remarkably scant. In central Australia, the chewing of wild Nicotiana spp., a tobacco plant, commonly known as pitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“… WHO World Health Organization, TSNA tobacco-specific nitrosamines a Figures are adapted from [ 1 , 2 , 18 23 ] …”
Section: Introductionmentioning
confidence: 99%
“… WHO World Health Organization, TSNA tobacco-specific nitrosamines a Figures are adapted from [ 1 , 2 , 18 23 ] …”
Section: Introductionmentioning
confidence: 99%
“…Pituri is the most common form of ST product used by the Australian Aboriginal population, and its consumption usually continues throughout pregnancy, childbirth and lactation. 7 Although some women quit tobacco use when they learn about their pregnancy, many return to smoking following birth. A systematic review conducted by Jones et al 8 in 2016 showed that only 13% of women were able to stop smoking throughout pregnancy, and of these 43% restarted smoking by 6 months post partum.…”
Section: Introductionmentioning
confidence: 99%
“…Pituri is the most common form of ST product used by the Australian Aboriginal population, and its consumption usually continues throughout pregnancy, childbirth and lactation. 7 …”
Section: Introductionmentioning
confidence: 99%
“…In central Australia, Nicotiana spp. is commonly used as chewing tobacco by Aboriginal women [57]. The Nicotiana spp.…”
Section: Introductionmentioning
confidence: 99%
“…Botanical analysis of Australian Nicotiana spp. demonstrates nicotine concentrations as high as 8 mg/g [3], and analysis of commonly used wood ash demonstrates high alkalinity (pH’s > 12.0 [57]) indicative of their ability to assist extraction and absorption of nicotine and related compounds during chewing [58].…”
Section: Introductionmentioning
confidence: 99%